Rural and historical tourism in Dobrugea - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
By its geographical location, the rural area from Dobrudgea has a diversified tourism potential, provided by the contrasting natural environmental factors, ranging from the oldest to the youngest relief units, natural protected areas, balneary resources and cultural, historical, religious sites, as well as multicultural local customs and traditions of the rural area. This potential can be used under various forms in the rural area: cultural tourism, historical tourism, religious tourism, ecotourism, fishing tourism or bird-watching tourism, as well as other kinds of rural tourism. By linking these tourism resources and tourism forms, tourism routes can result, which, together with the local customs, traditions and cuisine may contribute to the social and economic development of Dobrudgea's rural area, through sustainable tourism as an alternative to seasonal seashore tourism.
Keywords: 330; sustainable tourism; rural area; economic development; Dobrudgea